Penerapan Program Child Care sebagai Praktik CSR di Perusahaan Indonesia - Aprilia, Nadya Putri; Raharjo, Santoso Tri; Resnawaty, Risna (Journal Pemberdayaan Masyarakat Indonesia, 2024)
Corporate Social Responsibility is a commitment from a company to give more contribution to society, either through social action or environmental responsibility. In Indonesia, CSR is now stated more firmly in the Limited Liability Company Law (UUPT) Article 74 No.40 of 2007. CSR is also a company action in solving existing social problems, one of which is the problem of children. Problems with children within the company's scope occur internally (children of company employees) and externally (children of communities around the company). With these various problems, one type of CSR practice emerged in the form of a childcare program. In the social work literature, child care refers to the care of children at home in groups or in orphanages. This study aims to (1) find out how the implementation of childcare programs in CSR practices, (2) find out CSR practices in Indonesia that implement childcare programs. The method used in this research is the literature study method. Researchers conducted research from the results of a literature review of previously published literacy relating to CSR practices in the form of childcare programs in Indonesia.